Fluorescence of PDT Photosensitizers for Quantitative Cancer Diagnosis and Treatment Monitoring - Yeh, Shu-Chi (My University, 2015)
Photodynamic therapy (PDT) has been considered a favorable approach in certain oncology applications for its little invasiveness and better targeting specificity compared to conventional therapies. In PDT, localized photosensitizers can be activated by light to produce cytotoxic oxygen species. However, the prescribed drug and light doses do not provide satisfying outcomes as the PDT efficacy relies strongly on the interplay between localized dose factors. Therefore, the fluorescence emission from active photosensitizers has been investigated extensively for real-time PDT dosimetry. This dissertation focuses on characterizing fluorescence properties of two photosensitizers, Photofrin® and PpIX, in cellular models and discusses about their potential clinical applications. First, we introduc time-resolve fluorescence (TRF) of photosensitizers as a potential tool in PDT dosimetry. TRF acquires fluorescence decay profiles and it is sensitive to drug-microenvironment interactions that occur frequently in PDT. Therefore, it provides complementary information in addition to fluorescence spectra that could be subject to intensity artifacts. In this dissertation, we review TRF studies on PDT photosensitizers, and quantify TRF parameters of Photofrin® at various subcellular locations. Moreover, analytical solutions are developed to correct distorted TRF measurements from commonly used time-domain data acquisition. Second, we report a new concept – integrated detection and treatment of Barrett’s Esophagus (BE). BE is a pre-cancerous lesion considered as a major risk factor in developing esophageal cancers. However, early intervention of BE has remained a challenging issue as tissue biopsy introduces significant sampling errors and the separate procedures between diagnosis and treatment add relocation errors. We proposed to use PpIX fluorescence to highlight morphological features at the cellular level for quantitative classification, followed by well-characterized treatment. Current proof-of-concept studies were performed separately, whilst the detection and treatment can be integrated using confocal endomicroscopy technology. Overall, these studies examine the potential benefits provided by fluorescence of photosensitizers for cancer diagnosis and treatment monitoring.
Keywords: Fluorescence; Photodynamic therapy